Media in Improving Teachers Professional Competence at SMAN 5 Batam - Ermawalis; Fetri Yeni J; Darmansyah; Rayendra; Emilham Mirshad; Abdul Habib Arrasyidi Desky (Postgraduate, University of Mataram, 2025)
This study aims to analyze the use of digital-based media in enhancing the professional competence of teachers at SMAN 5 Batam. Teacher competence is crucial for improving the quality of learning, and digital technology offers potential strategies for professional development. The research employed a quantitative approach, using descriptive and inferential analyses, with simple linear regression to examine the relationship between digital media use and teacher competence. The results show that integrating digital media positively impacts teachers’ knowledge, pedagogical skills, and learning innovation. The study found a strong correlation between digital media use and professional competence (r = 0.770) and a coefficient of determination of 58.83%, indicating that digital media contributes significantly to competence improvement. Despite these positive outcomes, several challenges were identified, including limited infrastructure, insufficient ongoing training, and resistance to adopting new technologies. The findings suggest that the effective use of digital media can enhance teacher competence when supported by proper policies, continuous training, and capacity-building programs. This research highlights the strategic role of digital technology in teacher development and provides empirical evidence that supports the integration of digital media as a tool to foster professional growth and innovation in education.